The Tourism Landscape in Zlitin: Between Reality and Aspirations (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
Tourism is a modern phenomenon that has grown and developed with the development of societies. It is a natural wealth that remains if it receives care and attention and is exploited optimally, and an important industry because of its contribution to balancing the balance of payments, achieving a surplus from it, and thus strengthening the national economy, given that tourism revenues are from local or foreign currencies that tourists spend. In exchange for the tourism services they receive.A tourist country is one that has a cultural heritage or intellectual and cultural landmarks that enable scholars and amateurs to trace the story of a civilization that tells a period of time that has passed, and whose landmarks remain to express it.The study area is not isolated from this, as it is one of the regions of the country that possesses many of the elements that qualify it to be a tourist attraction, which vary among them, including Phoenician and Roman landmarks, historical shrines and fortresses, olive presses and mosques, all of which narrate an era that the city lived through in its various stages, in addition to the presence of... There are many natural components, such as the location and climate suitability for tourism in most seasons of the year, and the holding of seasonal festivals. However, the city has not received the necessary attention to advance its tourism field.
Keywords: The Tourism Landscape, Zliten, Tourism Economics, Archaeological Sites, and Obstacles